SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN MENU MAKANAN BERGIZI UNTUK IBU HAMIL DENGAN METODE FUZZY ANALYTICAL HIERARCHY PROCESS - Novhirtamely Kahar; Reny Wahyuning Astuti; Bagus Surya K (JURNAL AKADEMIKA)
Determination of nutrient intake in pregnant women is categorized as one example the case of multiple criteria, due to the capacity determination of nutrition, the diet of preg nant women is different, so do not rule out the possibility that making a decision is a very vital in determining the decisions to be taken on nutrition pregnant mother. Decision-making can be influenced by several aspects, it can affect the speed in taking decisions by decision makers when decision-making must be quick and accurate. This research aims to develop a decision support system for the selection of nutritious food for pregnant women using the method of Fuzzy Analytical Hierarchy Process (AHP). Fuzzy AHP method is an analytical method development of AHP. Although AHP is used in dealing with qualitative and quantitative criteria in AHP Fuzzy MCDM yet considered better in describing the decision vague than AHP. The system is built with the programmin g language delphi7 connected with PHPMyAdmin MySQL database. The input data in this system are: the data criteria and subcriteria, the food menu data, the data of pregnant women. While the output is on the food menu selection with election results or methods of Fuzzy AHP. The results showed that with a decision support system Fuzzy AHP method, pregnant women can determine the diet based on the recommendation.